2010
DOI: 10.20452/pamw.927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uncomplicated obesity on QT interval in young men

Abstract: INTROduCTION QT prolongation and obesity are associated with ventricular arrhythmia and sudden cardiac death. The relationship between uncomplicated obesity and QT inter val prolongation is not clear.ObjECTIvEs The aim of the study was to investigate the effects of uncomplicated obesity on QT inter val in young men.PATIENTs ANd mEThOds A total of 122 men, including 59 obese patients and 63 controls, were recruited into the study. Patients with hypertension, diabetes mellitus, and ischemic heart disease were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…The clinical significance of QTc and QT or QTc dispersion prolongation associated with obesity is uncertain. QTc and QT or QTc dispersion values, when prolonged in the studies included in this meta‐analysis, were generally modestly so . QTc values > 500 msec and QT or QTc dispersion values > 80 msec were rare .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The clinical significance of QTc and QT or QTc dispersion prolongation associated with obesity is uncertain. QTc and QT or QTc dispersion values, when prolonged in the studies included in this meta‐analysis, were generally modestly so . QTc values > 500 msec and QT or QTc dispersion values > 80 msec were rare .…”
Section: Discussionmentioning
confidence: 79%
“…Most of the studies in this meta‐analysis consisted predominantly or entirely of women . In the only study consisting entirely of men, mean QTc was significantly longer in 59 obese subjects than in 63 non‐obese controls . Park et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the mechanism of sudden cardiac death in this population is unknown, ventricular tachyarrhythmias are suspected to play a role (27,28). For this reason ventricular repolarization has been the subject of investigative interest in severely obese subjects as well as in those with less severe obesity (6,7,8,9,10,11,12,13,29,30,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Known causes of QTc prolongation include the congenital long QT syndromes, the Brugada syndrome, electrolyte disturbances (hypokalemia, hypomagnesemia, hypocalcemia), selected drugs (e.g., certain anti‐arrhythmic drugs, phenothiazines, tricyclic antidepressants, erythromycin in combination with certain antihistamines, pentamidine, and certain anti‐malarials), liquid protein and starvation diets, hypothyroidism, central nervous system lesions, severe bradycardia, mitral valve prolapse, acute myocardial infarction, and possibly obstructive sleep apnea (3,4,5). Multiple studies of obese subjects have reported prolongation of QTc and/or increased QT or QTc dispersion, suggesting an association between obesity and delayed ventricular repolarization (5,6,7,8,9,10,11,12,13). Patient populations in these studies were heterogeneous.…”
Section: Introductionmentioning
confidence: 99%